A chromosome-scale genome assembly for the holly (Ilex polyneura) provides insights into genomic adaptations to elevation in Southwest China. Issue 1 (5th January 2022) - Yao, Xin; Lu, Zhiqiang; Song, Yu; Hu, Xiaodi; Corlett, Richard T
Abstract: Southwest China is a plant diversity hotspot. The near-cosmopolitan genus Ilex (c. 664 spp., Aquifoliaceae) reaches its maximum diversity in this region, with many narrow-range and a few widespread species. Divergent selection on widespread species leads to local adaptation, with consequences for both conservation and utilization, but is counteracted by geneflow. Many Ilex species are utilized as teas, medicines, ornamentals, honey plants, and timber, but variation below the species level is largely uninvestigated. We therefore studied the widespread Ilex polyneura, which occupies most of the elevational range available and is cultivated for its decorative leafless branches with persistent red fruits. We assembled a chromosome-scale genome using approximately 100x whole genome long-read and short-read sequencing combined with Hi-C sequencing. The genome is approximately 727.1 Mb, with a contig N50 size of 5 124 369 bp and a scaffold N50 size of 36 593 620 bp, for which the BUSCO score was 97.6%, and 98.9% of the assembly was anchored to 20 pseudochromosomes. Out of 32 838 genes predicted, 96.9% were assigned functions. Two whole genome duplication events were identified. Using this genome as a reference, we conducted a population genomics study of 112 individuals from 21 populations across the elevation range using restriction site-associated DNA sequencing (RADseq). Most populations clustered into four clades separated by distance and elevation. Selective sweep analyses identified 34 candidate genes potentially under selection at different elevations, with functions related to responses to abiotic and biotic stresses. This first high-quality genome in the Aquifoliales will facilitate the further domestication of the genus.